The tumour microenvironment creates a niche for the self-renewal of tumour-promoting macrophages in colon adenoma - Soncin, Irene (2018)
Circulating CCR2+ monocytes are crucial for maintaining the adult tissue-resident F4/80hiMHCIIhi macrophage pool in the intestinal lamina propria. Here we show that a subpopulation of CCR2-independent F4/80hiMHCIIlow macrophages, which are the most abundant F4/80hi cells in neonates, gradually decline in number in adulthood; these macrophages likely represent the fetal contribution to F4/80hi cells. In colon adenomas of ApcMin/+ mice, F4/80hiMHCIIlow macrophages are not only preserved, but become the dominant subpopulation among tumour-resident macrophages during tumour progression. Furthermore, these pro-tumoural F4/80hiMHCIIlow and F4/80hiMHCIIhi macrophages can self-renew in the tumour and maintain their numbers mostly independent from bone marrow contribution. Analyses of colon adenomas indicate that CSF1 may be a key facilitator of macrophage self-renewal. In summary, the tumour microenvironment creates an isolated niche for tissue-resident macrophages that favours macrophage survival and self-renewal.